2011
DOI: 10.1016/j.virol.2011.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviruses induce autophagy to promote virus replication and oncolysis

Abstract: Adenoviruses with deletion of E1b have been used in clinical trials to treat cancers that are resistant to conventional therapies. The efficacy of viral replication within cancer cells determines the results of oncolytic therapy, which remains poorly understood and requires further improvement. In this report, we show that adenoviruses induce autophagy by increasing the conversion of LC3-I to LC3-II and the formation of the Atg12-Atg5 complex. Inhibition of autophagy with 3-methyladenine (3MA) resulted in a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 29 publications
(51 reference statements)
5
119
0
Order By: Relevance
“…Viruses could regulate autophagy in infected cells, but detailed mechanisms are elusive and may vary with virus types (8,28,44,67,68). Tobacco mosaic virus and hepatitis C virus (HCV) can induce autophagosome formation by inducing endoplasmic reticulum stress (29,53).…”
mentioning
confidence: 99%
“…Viruses could regulate autophagy in infected cells, but detailed mechanisms are elusive and may vary with virus types (8,28,44,67,68). Tobacco mosaic virus and hepatitis C virus (HCV) can induce autophagosome formation by inducing endoplasmic reticulum stress (29,53).…”
mentioning
confidence: 99%
“…We have previously shown that autophagy increases adenovirus replication by degrading intracellular components for building progeny virus particles. 39 Therefore, autophagy is unlikely to play an important role in I3C-reduced Ad replication.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation of the relatively low transduction efficiency of Ad5/F35 may be due to the longer stay at endosomal/lysosomal compartments without endosomal escape for nuclear import, resulting in less efficient Ad5/F35-mediated gene transfer compared to that of Ad5 (41). We therefore investigated other means of enhancing Ad5/F35 transduction efficiency, on the basis that the CD46 receptor-promoted autophagy would result in the promotion of viral replication and oncolysis (23). The chimeric Ad5/F35 adenoviral vector exerted a more significant oncolytic effect on cancer cells with a higher survival potential under autophagic conditions generated by pre-treatment with rapamycin (an mTOR inhibitor) as an autophagy inducer (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm that the transduction efficiency of Ad5/F35 and the levels of CD46 were not the main factors responsible for optimal gene transfer, we investigated the possibility that autophagy facilitates a faster induction of Ad5/F35 viral particle production compared to Ad5. According to recent studies, adenovirus has the ability to induce autophagy (36-39); therefore, autophagy may be used to facilitate the release of viral progeny, promote adenovirus replication and improve oncolysis (23,39).…”
Section: Expression Levels Of Car and Cd46 In Human Cancer Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation